Penerapan Model Pembelajaran Kooperatif Tipe Stad ( Student Teams Achievement Division) untuk Meningkatkan Hasil Belajar IPS di Kelas IV SD Negeri 3 Tondano - Korompis, Fransiska; Karamoy, Syuul T.; Nataratudio, Tiara (Peneliti.net, 2023)
This research was motivated by the low learning outcomes of students in the social studies learning process carried out in class IV of SDN 3 Tondano. This is caused by many things, including a lack of student motivation to learn, and a lack of teacher diversity in using learning methods. Based on the initial test carried out by researchers on 22 students regarding the subject of Artificial Natural Appearances in Indonesia in social studies learning, there were 8 students who got scores between 75 - 80 or in accordance with the KKM achievements determined by the school. This means that: 8/22 x 100% = 36.0% who understand, and there are still 14 students who have not reached the KKM score or 14/22 x 100% = 64.0% who do not understand the material on Artificial Natural Appearances in Indonesia This research is focused on studying the implementation of learning, student activities and student learning outcomes using the STAD (Student Teams Achievement Division) Cooperative Learning Model. The method used is Classroom Action Research, which is a form of reflective research carried out by researchers. , by conducting action research that is carried out directly in the classroom. The aim is to improve the quality of learning, especially in social studies learning in elementary schools. Based on analysis and reflection carried out in two cycles using the STAD Type Cooperative Learning Model (Student Teams Achievement Division). When compared between initial abilities and after taking action, it shows an increase. This can be seen from the student learning outcomes in cycle I which obtained an average score of 59.25%, and in cycle II obtained an average of 87%. Thus, the use of the STAD (Student Teams Achievement Division) Cooperative Learning Model in Social Sciences learning can improve student learning outcomes.